A novel mechanical metamaterial with simultaneous stretching- and compression-expanding property. (October 2021) - Wu, Wenjun; Liu, Pai; Kang, Zhan
Graphical abstract: Highlights: A novel metamaterial with simultaneous stretching- and compression-expanding property is designed and fabricated. A new stiffness switching mechanism is realized by exploiting contact nonlinearity. The metamaterial can exhibit positive, negative, and zero Poisson's ratio under loads in different directions. The unit cell configuration is also extended to 3D metamaterials and metastructures. This study demonstrates the potential of exploiting the contact nonlinearity in the design of novel mechanical metamaterials. Abstract: Poisson's ratio is an important property defining the relationship between lateral and longitudinal deformations. While most conventional materials have positive Poisson's ratios, auxetic metamaterials exhibit negative Poisson's ratios and will contract laterally under vertical compression and expand laterally under vertical tension. In this study, we develop a new type of mechanical metamaterial, which always undergoes lateral expansion regardless of the sign of the uniaxial load. The unit cell configuration is presented by combining a re-entrant negative Poisson's ratio structure and a hexagonal structure. A new stiffness- and deformation mode-switching mechanism is realized by exploiting contact nonlinearity in the unit cell configuration design. This novel metamaterial can exhibit positive, negative and zero Poisson's ratios under different loading directions. Its mechanical properties are verified through numerical simulations and experimental tests. The unit cell configuration is also extended to 3D metamaterials and metastructures. This study demonstrates that certain desired mechanical properties can be achieved by introducing contact nonlinearity and deformation mode switching into metamaterial design.